2014
DOI: 10.3390/educsci4040229
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of the Increased Tuition Fees on Academic Staffs’ Experiences in Post-92 Universities: A Small-Scale Qualitative Study

Abstract: The introduction of the new tuition fee regime in the UK academic session 2012-2013 has resulted in concerns in the Higher Education (HE) community that students' expectations may become unmanageable. Previous research has explored the expectations and experiences of undergraduate psychology students; the current study extended this by considering whether the increased tuition fees have changed the experiences of academic staff in HE. To achieve this, five semi-structured interviews with psychology staff in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Similarly, other research has suggested that students have largely vocational orientations towards university (Lehmann 2009), and that usefulness and applicability of course for future career are highly important in motivating choice of course (Jian et al, 2010). This is consistent with findings that job prospects are important to students when choosing to attend Higher Education (Krutii and Fursov 2007;Loeber and Higson 2009), and are perceived to be key expectations of university particularly for students paying higher fees (Bates and Kaye 2014a;2014b). It seems therefore that students are largely motivated by career-focused factors, particularly when considering vocational courses.…”
Section: Reasons For Attending Higher Educationsupporting
confidence: 76%
“…Similarly, other research has suggested that students have largely vocational orientations towards university (Lehmann 2009), and that usefulness and applicability of course for future career are highly important in motivating choice of course (Jian et al, 2010). This is consistent with findings that job prospects are important to students when choosing to attend Higher Education (Krutii and Fursov 2007;Loeber and Higson 2009), and are perceived to be key expectations of university particularly for students paying higher fees (Bates and Kaye 2014a;2014b). It seems therefore that students are largely motivated by career-focused factors, particularly when considering vocational courses.…”
Section: Reasons For Attending Higher Educationsupporting
confidence: 76%
“…A higher concentration enables collusion between firms, which can lead to higher profits. Firm effect models argue that differences in profitability exist and persist, and may derive from firm-level characteristics such as operating efficiency, organizational structure or quality of management (Bates and Kaye, 2014; Shahijan et al , 2016; Varghese, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a casestudy of a research-intensive university, Skelton (2012a) found that lecturers employ a strategic compromise around the differences between personal values and institutional aims. However, the extent to which lecturers working in post-1992 institutions 3 -who are traditionally more teaching-oriented -can also resist, challenge or negotiate consumer-oriented institutional pressures merits further research (see Bates and Kaye 2014a). The concern here is that not only are lecturers losing teaching autonomy, there are also increasing expectations that lecturers should be mindful of student satisfaction, which can create tension between pedagogies for critical learning and teaching to just passing or pleasing students (Ek et al 2013;Kreber 2010).…”
Section: Teaching In Higher Educationmentioning
confidence: 99%